The Symbolic Structure of Andrei Bely's Pervoe svidanie: Echoes of Wagner and Steiner - Wells, David (W. Maney/UCL School of Slavonic and East European Studies, 2003)
This article examines two particular elements that inform the symbolic structure of Pervoe svidanie and investigates how they combine to further Belyi's thematic aims. The first of these is the Wagnerian concept of leitmotiv; the second is a view of spiritual education derived substantially from theosophical and anthroposophical thought and particularly from the ideas of Rudolf Steiner. The two intersect in the colour imagery that Belyi employs in his poem, which becomes not only a major source of its emotional and structural unity, but also a vehicle for the integration of the poem's realist and symbolic impulses.